Screening and identification of forage sorghum (Sorghum bicolor) cultivars for ethanol production from stalk juice* - PRASAD, SHIV; JOSHI, H C; JAIN, N; KAUSHIK, R (The Indian Journal of Agricultural Sciences, 2011)
Sorghum biomass is a renewable resource that offers significant potential for ethanol production. Nine sorghum cultivars (forage type) were screened for ethanol production potential during 2004-05 at IARI, New Delhi. ’PCH 109’ recorded the highest stalk and sugar yield followed by ’PC 615’, and ’PC 6’ whereas the lowest was in cultivar ’PC 23’. Juice recovery in sorghum stalks varied from 27.3 to 40.1 %. The maximum ethanol yield was recorded in cultivar ’PCH 109’ (1 661 litreha in one crop cycle and 3 236 litreha in two crop cycles) and minimum was in ’PC 23’ (814 litreha in one crop cycle). Sorghum cultivar ’PCH 109’ was most suitable and eficient for ethanol production with maximum fermentation efficiency and could be used for ethanol production from stalk juice in the distilleries throughout the year in subtropical climatic condition of north India. The underutilization of the existing molasses-based ethanol distilleries and the future deficit in ethanol requirement of the country can be met if sorghum cultivation is promoted for ethanol production.